METHODS OF SPEECH DEVELOPMENT OF PRIMARY CLASS STUDENTS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The article provides a number of tips for speech development in the concept of speech development, grade mother tongue and reading literacy classes.